Saccharomyces cerevisiae Cell wall Effects on Immunological Response Of Broiler Chicks that Infected with Listeria monocytogenes: Faris A. Al- Obaidi ,Al- Nassery, Ban S. Abdul- Nabi and ,Shahrazad M. Al- Shididi - Al- Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2010)
The objects of this study were to determine the effect of Saccharomycescerevisiae cell wall (SCCW) to induce immunological response of Broiler chicks thatinfected with Listeria monocytogenes . SCCW was administrated to chicks by adding30 gm / 100 kg feed. A 30 broiler chicks were distributed into 3 treatments ( 10chicks/ treatment) which were:T1 : control group for both experiment fed on (SCCW). T2 : chicks fed 30 gm / 100 kgfeed (SCCW) and experimentally infected orally by Listeria monocytogenes 0.1 mlof 1 × 109 CFU /ml. T3 : chicks were experimentally infected orally by Listeriamonocytogenes 0.1 ml of 1 × 109 CFU /ml. and study some immunological parameterincludes the concentration of  - globulin, albumin, transfferin, H/L ratio, singlediffusion test, delayed hypersensitivity reaction (DWR). The result obtained revealedthat using (SCCW).increased immune response (cellular and humeral immunity)through increased of lymphocyte and decreased H/L ratio and positive reaction ofdelayed hypersensitivity also increase the percentage of  - globulin, albumincompared with infected group (T3).